Pulmonary vascular and airway changes in previously hospitalised COVID-19 patients: long-term functional respiratory imaging findings correlate with reduced DLCO - Svensson, Ann Mari; Björnson, Mikael; Sköld, Magnus; Kauczor, Hans-Ulrich; Nygren-Bonnier, Malin; Bruchfeld, Judith; Runold, Michael; Kistner, Anna; Nyrén, Sven (PLOS ONE, 2025)
Background Persistent respiratory symptoms in COVID-19 patients have raised concerns about structural remodelling in the lung. We assessed structural changes and their correlation with reduced DLCO, eight months after discharge, in previously hospitalised COVID-19 patients. Materials and Methods An exploratory observational study was conducted on 26 male patients (mean age: 60 years, range: 50-69) previously hospitalised for COVID-19. CT scans, performed eight months post-discharge, were analysed using functional respiratory imaging (FRI) to assess lung structure and function. Analyses were made based on diffusion capacity for carbon monoxide (DLCO). Results Patients with low DLCO (≤75%; n = 9) exhibited a significantly lower proportion of small blood vessels with a cross-sectional area < 5 mm² compared to patients with normal DLCO (>75%; n = 17) (median (IQR) 56 (51-59) % vs. 60 (56-64) %, p = 0.008), as well as a reduced absolute volume of small vessels with a cross-sectional area < 5 mm² (129 (121-151) ml vs. 155 (132-175) ml, p = 0.025). Bronchial dilatation was more evident in the low DLCO group, with a higher ratio of airway volume to lobar volume (siVaw) (149 (138-165) % vs. 117 (93-132) %, p = 0.002). SiVaw showed a significant inverse relationship with DLCO (r = -0.56, p = 0.004, R² = 0.31). Lobar volumes were reduced in both DLCO groups, and more pronounced in the low DLCO group (72 (65-81) % vs. 90 (79-95) %, p = 0.001), as was total lung capacity (TLC) (73 (64-85) % vs. 92 (85-98) % of predicted, p = 0.003). FEV₁/FVC ratios were elevated in both groups, with a potential difference observed between the low and normal DLCO groups (110 (103-118) % vs. 105 (95-113) %, p = 0.074). Conclusions We demonstrate long-term vascular and airway remodelling detected with FRI in previously hospitalised COVID-19 patients and highlight potential mechanisms underlying persistent pulmonary dysfunction and emphasise the need to investigate the underlying pathophysiology to identify potential individualised treatment strategies for this patient group.
Online veröffentlicht: 2. Dezember 2025
Gesehen am 27.02.2026